Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Partisipasi Belajar Siswa dalam Pembelajaran IPAS Kelas IV SD - Rusniasari, Rusniasari; Ermawati, Diana; Khairunnisa, Imada (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2025)
Low learning participation is the main problem in the learning of science for grade IV students Elementary School of Demangan. This classroom action research aims to increase student learning participation through the application of the role playing learning model. The research method used is Classroom Action Research (CAR) which is carried out in two cycles. The subjects in this study were 14 grade IV students Elementary School of  Demangan. The data analysis method in this study used a descriptive method by comparing student participation before and after the action. The results showed an increase in learning participation from the pre-cycle of 50.1%, cycle I of 63.3%, and cycle II reaching 81.3%, which is in the very high category. This increase shows that the role playing model is effective in creating a pleasant learning atmosphere and encouraging active involvement of students in the learning process. Thus, the role playing model can be used as an alternative strategy for learning science that can significantly increase student learning participation